Large-scale evaluation of students with special educational needs in the city of Londrina (PR) - Mariana Cesar Verçosa Silva; Silvia Márcia Ferreira Meletti (Universidade Federal de Santa Maria (UFSM), 2012)
This research aims to analyze the rates of school performance and attendance in large-scale assessments of special educational needs students included in the regular school system in the city of Londrina-PR, in 2007. For this, we used microdata from Brazil Proof (2007) and Enem (2007) provided by the National Institute for Educational Studies and Research Teixeira-INEP. This proposal focuses on the analysis of data from the variables: type of special educational need, sex, race, age, and frequency on the test performance. The results show that despite the implementation of inclusive policies, participation of pupils with special educational needs in large-scale assessments is minimal, which denotes the idea of ambiguity between speech and inclusive practice.